A Distributed Algorithm for Least Squares Solutions - Wang, Xuan; Zhou, Jingqiu; Mou, Shaoshuai; Corless, Martin J. (IEEE transactions on automatic control, 2019)
In this technical note, a distributed algorithm is proposed for multiagent networks to achieve a least squares solution of a system of linear equations, in which each agent only knows part of the overall equations and communicates only with its nearby neighbors. The proposed algorithm is discrete time but does not involve small or time-varying step sizes. Given that the network is fixed, connected, and undirected, the proposed algorithm enables all agents in the network to achieve exponentially fast the same least squares solution; this is validated by simulations.